Teenagers with ADD and ADHD : a guide for parents and professionals - Zeigler Dendy, Chris A. 4 0 16; 5 (Bethesda, MD : Woodbine House, 2006)
Offers parents practical strategies to help them cope with the challenges associated with raising a teenager with ADHD and ADD, with information and tips on diagnosis, school, treatments, coexisting conditions, behavior issues, medications, and other related topics.
Includes bibliographical references and index.
Adult.
Keywords: 2 -- 0; 6; Attention-deficit disorder in adolescence;Attention-deficit hyperactivity disorder. -- Popular works; 20; 2